Phase evolution in two-phase alloys during severe plastic deformation. (15th May 2021) - Pant, Nirab; Verma, Nisha; Ashkenazy, Yinon; Bellon, Pascal; Averback, Robert S.
Abstract: Phase evolution in FCC metals with strongly interacting alloy components during severe plastic deformation is investigated using molecular dynamics simulations. Specifically, we study the alloy microstructure in steady state, nucleation and growth of precipitates in supersaturated alloys, and the dissolution of precipitates in undersaturated alloys. The results are compared to a modified effective temperature model, providing a physical understanding for the atomic processes underlying the model and a perspective on its strengths and weaknesses. Key observations in this work are nucleation and growth of precipitates during SPD at a temperature of 100 K; Gibbs-Thomson-like behavior relating steady-state solubility to precipitate size under sustained shearing; a direct relationship between the effective temperature and the shear modulus; and the importance of cluster agglomeration during precipitate growth. The study also reveals that the mechanism of forced chemical mixing depends on precipitate size, adding complications for effective temperature models describing inhomogeneous systems. The simulations are shown to provide good semi-quantitative agreement with experimental findings reported in the literature. Graphical abstract: Image, graphical abstract